ABCC2 Haplotype is Associated With Antituberculosis Drug-Induced Maculopapular Eruption - Kim, Sang-Heon (The Korean Academy of Asthma, Allergy and Clinical Immunology; The Korean Academy of Pediatric Allergy and Respiratory Disease, 2012)
Genetic variants in ATP-binding cassette (ABC) transporter genes are associated with increased susceptibility to adverse drug reactions. We hypothesized that genetic variant ABC transporters (ABCB1 and ABCC2) may be candidate markers for predicting maculopapular eruption (MPE) induced by antituberculosis therapy. We compared the genotype distributions of single nucleotide polymorphisms and haplotypes in the ABCB1 and ABCC2 genes between 62 antituberculosis drug (ATD)-induced MPE cases and 159 ATD-tolerant controls using multivariate logistic regression analysis. There was no significant association between genetic polymorphisms in ABCB1 and ATD-induced MPE (P>0.05). Among seven selected SNPs of ABCC2, IVS3-49C>T in intron and I1324I were associated with ATD-induced MPE (P=0.029 and 0.036, respectively). In an analysis of the ABCC2 haplotypes (ht; -1549G>A_-24C>T_IVS3-49C>T_V417I), ht1[G-C-C-G] was significantly associated with ATD-induced MPE (P=0.032, OR=0.35, 95% CI: 0.16-0.95). No significant association between the other haplotypes and ATD-induced MPE was observed. An ABCC2 haplotype is associated with the presence of ATD-induced MPE in patients with tuberculosis and may be a genetic risk factor for the development of MPE induced by ATD.